Strategi Diferensiasi Produk dalam Mencapai Keunggulan Bersaing CV Tirta Emas - Cica Permata Sari; Alifian Nugraha (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study discusses the differentiation strategy that has been carried out at CV Tirta Emas. The differentiation strategy is an effort made by the company by providing a differentiator between its products and market products. Businesses have different characteristics so that they are easily recognized by the public. CV Tirta Emas has a distinctive feature in its products, namely comfortable noodle products which are one of the healthy foods. The results of the observation show that one of the factors in the differentiation strategy carried out is still not optimal, which results in a less stable sales turnover received in 2023. This study aims to analyze the product differentiation strategies carried out in achieving competitive advantage. In this study, the author uses the theory put forward by Feranita that there are six factors that can be done in carrying out a differentiation strategy to achieve competitive advantage. Excellence can be measured from the uniqueness, quality and selling price of the product. The method used is a qualitative descriptive case study method by producing data from competent sources. Data collection is carried out by conducting observation, interview and documentation techniques. The essence of this study is to maintain the differentiation strategy that has been implemented and analyze the differentiation strategy in achieving the competitive advantage of CV Tirta Emas.